Engineering simulations of a super-complex cultural heritage building: Ica Cathedral in Peru - Ciocci, Maria Pia (2018)
The Cathedral of Ica, Peru, is one of the four prototype buildings involved in the ongoing Seismic Retrofitting Project, initiative of the Getty Conservation Institute. The complex historical building, which was heavily damaged by earthquakes in 2007 and 2009, can be divided into two substructures: an external masonry envelope and an internal timber frame built by a construction method known as quincha technique. This study makes use of the information available in literature and the results obtained from experimental campaigns performed by Pontificia Universidad Catlica del PerA and University of Minho. Nonlinear behaviour of masonry is simulated in the numerical models by considering specified compressive and tensile softening behaviour, while isotropic homogeneous and linear behaviour is adopted for modelling timber with appropriate assumptions on the connections. A single representative bay was initially studied by performing linear elastic analysis and verifying the compliance with the various criteria specified by the applicable normative to discuss the actual failure of Ica Cathedral. Afterwards, the structural behaviour of the two substructures composing the Cathedral is evaluated independently. Finally, the interaction of these two substructures is investigated by performing structural analysis on the entire structure of Ica Cathedral. Several structural analysis techniques, including eigenvalue, nonlinear static and dynamic analyses, are performed in order to: (1) evaluate the dominant mode shapes of the structure; (2) validate the numerical models by reproducing the structural damage observed in situ; (3) estimate the structural performance; and (4) identify the main failure mechanisms.